2019
DOI: 10.1186/s12967-019-2102-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prognosis, genome, microbiome, and microbial metabolome in different sites of colorectal cancer

Abstract: Background: The colorectum includes ascending colon, transverse colon, descending colon, sigmoid colon, and rectum. Different sites of colorectal cancer (CRC) are different in many aspects, including clinical symptoms, biological behaviour, and prognosis. Purpose: This study aimed to analyse prognosis, genes, bacteria, fungi, and microbial metabolome in different sites of CRC. Methods: The Surveillance, Epidemiology, and End Results (SEER) database and STAT were used to statistically describe and analyse the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Most published studies have used to consider TCC as part of the RCC, although tumors arising from the transverse colon, according to its embryological origins, may share characteristics with right colon cancer (RCC) as well as with left colon cancer (LCC) [1,[15][16][17]. Thus, it is still not completely clear if TCC behavior is more like to right-sided rather than left-sided ones or if it has its clinicopathological features and a different clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies have used to consider TCC as part of the RCC, although tumors arising from the transverse colon, according to its embryological origins, may share characteristics with right colon cancer (RCC) as well as with left colon cancer (LCC) [1,[15][16][17]. Thus, it is still not completely clear if TCC behavior is more like to right-sided rather than left-sided ones or if it has its clinicopathological features and a different clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…42 Our previous study also demonstrated that the levels of SCFAs in CRC patients and individuals with a high risk of CRC were higher than those in healthy individuals. 8…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…6 Recent studies have shown that changes in the gut microbiota could be a major factor to trigger CRC. 7,8 There are many types and numbers of microorganisms in the intestinal tract. They can participate in the substitution of sugar, protein, starch, vitamins, and other nutrients to determine the body's immune function and maintain the health of the host.…”
Section: Introductionmentioning
confidence: 99%
“…We can only speculate whether the prolonged exposure of tumour mucosa to predominantly stool bacteria that is mechanistically related to tumours in distant part of the colon (left-sided or with onset in rectosigmoid and rectum) can have potentially harmful or bene cial effects or whether any associations are mostly due to the well-known molecular differences in the right vs left sided tumours [32,63,94].…”
Section: Tumour Crc Microbial Subtypesmentioning
confidence: 99%